The Influence Of The Work Environment On Employee Performance Through Work DisciplineAnd Job Satisfaction In The Education - Mustaqin Musma; Gunawan Gunawan; Bahtiar Bahtiar (Vifada Management and Digital Business, 2025)
This study aimed to analyze and describe the influence of the work environment on work discipline, job satisfaction, and employee performance. It also examined the influence of work discipline and job satisfaction on employee performance, as well as the influence of the work environment on employee performance through work discipline and job satisfaction at the South Sulawesi Provincial Education Office. This research was conducted at the South Sulawesi Provincial Education Office for approximately two months, from December to February 2026. The approach used in this study was quantitative, with 125 respondents, all employees. A questionnaire containing questions with a Likert scale was used to represent respondents' opinions, and descriptive analysis was used to provide an overview of the research variables derived from respondents' answers.   The results showed that the work environment directly had a positive and significant influence on work discipline and job satisfaction. The work environment had a positive and significant influence on employee performance. Work discipline has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Furthermore, the work environment has a positive and significant effect when mediated by work discipline and also when mediated by job satisfaction